Dtection of IFN-Y +874tla gene polymorphism and p/asmodtum falciparum infection ln ardamata idp camp, Al-Geneina city Sudan - Osman, Yahye Elmi (2020)
Malaria is the primary parasite disease and is responsible for around 214 million infections annually, resulting in more than 438,000 deaths. In Sudan, Plasmodium falciparum is typically accountable for severe malaria. Cytokine gene polymorphisms can alter the development of these proteins and therefore affect the immune response to disease. Interferon- (IFN- ), a pro-inflammatory cytokine, has been shown to have antiparasitic and immunopathogenic effects during malaria infection. A single nucleotide polymorphism (SNP), +874T/A, in the first intron of the IFN- gene, has presented associations with human susceptibility to many diseases, including malaria in certain populations. Therefore, the purpose of this study was to investigate whether genetic variation at the IFNG locus (IFN-+874T/A gene) affects susceptibility to P. falciparum malaria infection in the Sudanese population. Thirty-four (34) dried blood samples of Sudanese communities from the Ardamata IDP Camp in Al-Geneina Town, Sudan were first confirmed with nested PCR for malaria positive confirmation and Plasmodium falciparum identification. PCR was then used to test the relationship between P. falciparum infection and IFN- +874T/A gene polymorphism of the samples. The result of the nested PCR showed that out of 34 samples, 17 samples were malaria positive and P. falciparum positive, and 17 samples were negative. However, our result suggests that the IFN- +874T/A mutation has no association with P. falciparum infection. In conclusion, this data offers a starting point for functional and genetic analysis of the IFN-γ genomic region in malaria infection affecting Sudanese populations, which will promote the potential production of successful malaria vaccines.